2016
DOI: 10.1159/000453599
|View full text |Cite
|
Sign up to set email alerts
|

Nordic Walking and the Isa Method for Breast Cancer Survivors: Effects on Upper Limb Circumferences and Total Body Extracellular Water - a Pilot Study

Abstract: Background: The negative side effects of breast cancer treatments can include upper limb lymphoedema. The growing literature indicates that Nordic walking is an effective discipline against several disease symptoms. The aim of this study was to determine whether introduction to Nordic walking alone is effective against total body extracellular water and upper limb circumferences in breast cancer survivors compared to its combination with a series of specifically created exercises (i.e. the Isa method). Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 6 publications
0
27
0
Order By: Relevance
“…The initial search resulted in the finding of 76 investigations. After reading the titles and the abstracts, 36 potential studies were identified, 9 of which were included in the final analysis (Figure ; Di Blasio, Morano, Bucci, et al, ; Di Blasio, Morano, Napolitano, et al, ; Fields, Richardson, Hopkinson, & Fenlon, ; Fischer et al, ; Hanuszkiewicz, Malicka, Barczyk‐Pawelec, & Woźniewski, ; Hanuszkiewicz, Malicka, & Woźniewski, ; Jönsson & Johansson, , ; Malicka et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The initial search resulted in the finding of 76 investigations. After reading the titles and the abstracts, 36 potential studies were identified, 9 of which were included in the final analysis (Figure ; Di Blasio, Morano, Bucci, et al, ; Di Blasio, Morano, Napolitano, et al, ; Fields, Richardson, Hopkinson, & Fenlon, ; Fischer et al, ; Hanuszkiewicz, Malicka, Barczyk‐Pawelec, & Woźniewski, ; Hanuszkiewicz, Malicka, & Woźniewski, ; Jönsson & Johansson, , ; Malicka et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The ES of the different studies is presented in Table . The study from Di Blasio, Morano, Napolitano, et al, () did not report sufficient data to calculate the ES.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations